KNOWLEDGE SHARING BERBASIS KARAKTER PEMUSTAKA - Tri Hardiningtyas (Central Library of Universitas Sebelas Maret, 2016)
This research discusses about knowledge sharing based on user’s character. The objectives are to measure part of user’s character indicators that supporting knowledge sharing as: honesty, opennes, and responsibel. These can used as tools to improve usability of library and their service, such as: prime services, increasing user skills to access library services, increasing librarian skill to manage all library resources and disciplining the librarians and users toward serve based on user desire.